Konsep Doa Yesus Menurut Kallistos Ware: Sebuah Doa Yang Mencapai Kesempurnaan - Chrisnatalia Hia; Syutriska Kardia Gulo (Journal Of Spirituality And Practical Theology, 2024)
Prayer is an important aspect of human life, especially Christians. However, sometimes people pray when they are in trouble and suffering from what they are experiencing and then they need God in their lives. For this reason, the aim of the research is to explain the true power of the Jesus puja prayer and why this prayer has become an important part of Christian life based on the book written by Kallistos Ware from Diokleia. The method used by the author in this research is a literature study with a descriptive qualitative approach where the book "The Power of the Name of the Jesus Prayer in Orthodox Spirituality" is the most important book in this research. The author also collaborates with other sources such as journals, the Bible and the writings of the church fathers. The results of this research show that the Jesus puja prayer can be used anytime and anywhere or in situations that are not possible for someone, and this prayer can also help people to establish good communication with God, so that the relationship between humans and God remaining firm in faith that achieves salvation and likeness to God or achieves theosis.